Performance Analysıs of A Hybrıd Energy System - Sancy Isaac George, Tushar (International Journal of Advanced Science and Technology, 2020)
The largest production of electricity takes place through combustion of fossil fuels. As a result of this, these resources are depleting rapidly and are having a detrimental impact on the environment. Recently there has been surge in emphasis being laid on alternative sources of power generation through solar cells and wind turbines. Thus, it is imperative for organizations to think of an alternative, adopt greener technologies, to cut their costs and benefit the environment as well. A hybrid system involves multiple options to generate electricity, as a result of which analysis of the system becomes quite complex. These hybrid generation systems are designed to function in two ways, as a standalone system, which without being connected to the electricity grid supplies power to a set of loads, or as a grid-connected system, where a system undergoes transmission and distribution, to be integrated to the grid. The paper implements HOMER, iHOGA and RETSCREEN software tools for the design, analysis, optimization, and economic viability of the PV-Wind Hybrid Energy system. The daily load patterns were observed for the Microprocessor Lab in the Electrical Sciences Block, SRM UNIVERSITY, Potheri, Chennai , India over a month. Energy Management Strategy was tested with prototype for its effectiveness and has been verified with respect to software simulations. The results are validated with the help of a prototype.